Nitrogen-doped hollow carbon nanospheres for high-energy-density biofuel cells and self-powered sensing of microRNA-21 and microRNA-141. (February 2018) - Wang, Lin-Lin; Shao, Hao-Hua; Wang, Wen-Jing; Zhang, Jian-Rong; Zhu, Jun-Jie
Abstract: High-energy-density enzymatic biofuel cells (EBFCs) are urgently needed not only as green energy conversion devices but also as energy generators for medical devices. Low enzyme loading efficiency and insufficient direct electron transfer (DET) between enzymes and electrodes greatly hamper the development of EBFCs. Herein, we fabricated nitrogen-doped hollow carbon nanospheres with large pores (pNHCSs) via a green microwave-assisted hydrothermal method (MWHM). Due to their three-dimensional structure and the incorporation of nitrogen, the pNHCS-functionalized electrode not only efficiently enriched the load of enzyme (ca. 8.65 × 10 −10  mol cm −2 ) but also significantly facilitated DET rate (ca. 10.73 s −1 ). Thus, the pNHCS-based EBFCs exhibited an outstanding maximum power output (Pmax ), which achieved to 325 ± 0.6 µW cm −2 . Then, based on a dual-fuel-driven EBFC, we developed an innovative self-powered biosensor to sense two kinds of cancer-related microRNAs, miR-21 and miR-141, at the same time. The detection limits were as low as 0.1 fM for miR-21 and 4.0 fM for miR-141 (S/N = 3). This material has excellent potential in the development of superior green bio-batteries as well as economical and portable self-powered biomedical sensors. Graphical abstract: Highlights: An outstanding electrode material for enriching enzyme and facilitating DET rate is fabricated. The single-chamber EBFC exhibit remarkable power density of 325 ± 0.6 µW cm −2 . A self-powered biosensor for sensing miR-21 and miR-141 simultaneously is developed. The detection limits are as low as 0.1 fM for miR-21 and 4.0 fM for miR-141 (S/N = 3).